Evaluation of The School Literacy Movement Program at SMP Negeri 2 Serang Baru - Isnaeni, Ari; Baharuddin; Muthi, Ibn (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2023)
This study aims to evaluate the literacy program at SMPN 2 Serang Baru, Bekasi Regency. This research is evaluative with a descriptive qualitative approach using the CIPP method. The results of the study show1) Context evaluation, including background information, program implementation goals based on needs, and setting up cooperation with related agencies. 2) Evaluation of inputs, such as program development stages, activity schedules, the School Literacy Team, the availability of infrastructure, and program development costs 3) The stages of process evaluation are habituation, development, and learning. Literacy activities are done by teachers, school principals, and other education staff 4) Product evaluation shows the success of the program, namely the compatibility of targets with results, an increase in learning outcomes, and program benefits for schools. In conclusion, this program must be continued with various improvements and can be applied in other schools.